Jsc and Voc optimization of perovskite solar cell with interface defect layer using taguchi method - Bahrudin M.S.; Abdullah S.F.; Ahmad I.; Zuhdi A.W.M.; Hasani A.H.; Za'Abar F.; Malik M.; Harif M.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cadmium sulfide; Cadmium sulfide solar cells; Copper compounds; Cost effectiveness; Defects; Efficiency; Electric network analysis; Electron transport properties; II-VI semiconductors; Microelectronics; Open circuit voltage; Perovskite; Perovskite solar cells; Solar absorbers; Sulfur compounds; Taguchi methods; Tellurium compounds; Device simulations; Electron transport layers; Hole transport layers; Interface defects; L9 orthogonal arrays; Photonic structure; Solar cell absorbers; Taguchi optimizations; Solar cells